Korelasi antara Dukungan Keluarga dengan Grade Ulkus pada Penderita Diabetes Mellitus - Tiyara, Ervina; Witriyani, Witriyani; Mulyono, Puput (Universitas Muhammadiyah Klaten, 2025)
Background: Diabetes Mellitus (DM) is a chronic metabolic disorder characterized by persistent hyperglycemia, which frequently leads to severe complications such as diabetic ulcers resulting from peripheral neuropathy and microvascular angiopathy. These ulcers pose risks of tissue damage, recurrent infections, limited mobility, and even amputation if not adequately managed. They also impair patients’ quality of life while increasing psychological and financial burdens. Consequently, proactive preventive measures are critically needed. Family support plays a strategic role in the management of DM, particularly in aspects like foot care, adherence to pharmacological therapy, dietary regulation, and routine blood glucose monitoring. Objective: This study aimed to determine the correlation between family support and the incidence of ulcers in DM patients at UPT Puskesmas Gondangrejo, Karanganyar Regency. Methods: This research employed a quantitative design with a cross-sectional approach, involving 71 respondents. Research instruments included the Hensarling’s Diabetes Family Support Scale (HDFSS) and the Wagner Ulcer Classification System. Data were analyzed using the Spearman’s rho test. Results: The findings revealed a very strong and significant correlation between family support and ulcer incidence (p = 0.000; Rho = -0.957). The negative correlation indicates that higher family support is associated with a lower risk of ulcers. Conclusion: Adequate family support significantly contributes to reducing the risk of diabetic ulcers. Therefore, family-centered nursing interventions should be optimized to enhance diabetes management and improve patients’ quality of life.